A Combined Approach to Solving Applied Metal Forming Problems - Matvej Baldin; Nikita Kondratev; Peter Trusov; Kirill Ostapovich (Crystals)
This paper presents a combined approach to the solution of boundary value problems. The approach implies the joint application of a macro-phenomenological model and multilevel physical constitutive models for describing the behavior of a polycrystalline material. Within the framework of the proposed approach, the boundary value problem is solved for a certain product (structure) using a macro-phenomenological model of the material and the response in the chosen area is clarified using multilevel modeling techniques. The capabilities of the approach were demonstrated in a series of numerical experiments covering metal forming processes. In order to test and verify the proposed technique, in the first numerical experiment, the process of an upsetting of the sample was considered using only a multilevel physical model of the material and using the formulated combined approach. The response in the chosen domain was compared to the results obtained by different modeling approaches. The comparison showed good agreement in terms of the variables of the stress–strain state at the macro level, as well as in terms of the variables characterizing the internal structure of the material. At the same time, using the combined approach, the required computation time was reduced by more than 12 times. In the second and third numerical experiments, the process of sheet rolling and sample pressing was successfully simulated using a combined approach. The formulated approach is computationally efficient and applicable for solving the relevant boundary value problems of design and the optimization of technological processes.